MCM-41 as support for immobilization of NAR-1 bacterial consortium in the biodegradation of remazol black B - Ilan Sollan, Kogulabalan (2013)
A novel bacterial consortium, NAR-1 consisting of Enterococcus sp. C1 and Citrobacter sp. L17 was immobilised onto an inorganic support material and investigated for its biodegradation ability of Remazol Black B (RBB), microaerophilically under both batch and fed-batch continuous systems. To study its efficiency under immobilised condition, the NAR-1 bacterial consortium was adsorbed onto a silica mesoporous material, MCM-41 before conducting decolourisation experiments. Successful synthesis of MCM-41 was verified by FTIR, XRD and FESEM. The MCM-41 powder generated was granulated into spheres of 2-4mm in diameter before immobilisation. Preliminary immobilisation of NAR-1 was done conventionally by observing three parameters namely: agitation speed, contact time and operating temperature in 0.85% (w/v) saline. The highest adsorption of bacteria onto MCM-41 granules was 7.8 x 105cfu/ml at 100 rpm, 2 hours contact time and37oC.This preoptimised condition was transferred to RSM for a more precise prediction. RSM predicted a 7.8 x 105cfu/ml using an optimised condition of 1.9 h contact time at 34oC and 116 rpm but actual lab experimentusing the above parameters successfully produced a higher immobilised cell count of 9.0 x 105 cfu/ml. To compare the reusability of free and immobilised cells with both cell counts fixed at 9 x 105 cfu/ml, repeated-batch operation was conducted with constant addition of 100 ppm RBB into Modified P5 medium pH7.0, following each decolourisation cycle. Free cells initially took 240 min in the first cycle, declined to 180 min but yet again elevated to 270 min in the third cycle. It took a staggering 420 min to complete the 4th cycle of decolourisation. Improving decolourisation trend was observed from 180 min to 120, down to half the time at 60 min with immobilised cells. Eleven cycles were completed for immobilised cells as compared to 4 for free cells within a time-frame of 19 h. For continuous fed-batch system in an upflow packed bed reactor, the decolourisation rate progressively escalated from 50% within the first 3 hours to 80 % by the 8th hour. Interestingly, beyond that, stabilised decolourisation at almost 90 % was observed, spanning 28 h covering 9.49 cycles. A prominent decline was noticed after the 36th hour and the efficiency plummeted to 0% by the 56th hour. This sharp decline was conceivably due to several factors including bacterial leach out, bacterial cell death due to toxic accumulation and detachment of biofilm. However, MCM-41, an inorganic material remains as a potential support for bacterial immobilisation and can be applied repeatedly in a continuous system due to its rigidity.